(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article examines the structure, semantic features, and stylistic functions of appositive constructions as one of the essential categories of syntax. It highlights the role of apposition in expanding, clarifying, and supplementing the meaning of syntactic units. The study analyzes the use of secondary sentence parts—attributes, objects, and adverbials—as appositional components within different syntactic structures. Special attention is given to adverbial appositions expressed by prepositional nouns and their contribution to enriching the semantic layer of the text. The paper provides examples illustrating the communicative, expressive, and explanatory functions of appositive elements and discusses their significance in enhancing the emotional and stylistic value of speech.